Passive pressure-based universal connection method for ceramic materials

By coating the connecting slurry on the surface of the ceramic piece and clamping the C/C plate with low thermal expansion coefficient and the plate with differentiated thermal expansion coefficient on both sides, fixing it with C/C bolts, and sintering at high temperature to achieve the connection, the current solution is to be solved With the cost of ceramic material connection technology under high temperature and high pressure and the industrial production difficulties, the high bending strength and acid-base corrosion resistance of ceramic connectors have been achieved.

CN119430981APending Publication Date: 2025-02-14NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411412973.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing ceramic material connection technology needs to be carried out at high temperatures and high pressures, resulting in high connection costs and difficult to achieve industrial production.

Method used

Using a universal connection method of ceramic materials based on passive pressure, C/C bolts are used to coat the connecting slurry on the surface of the ceramic piece and clamp the C/C flat plate with low thermal expansion coefficient and differentiated thermal expansion coefficient on both sides, using C/C bolts Fixed and sintered at high temperature to achieve connection.

Benefits of technology

Reduces the dependence of connecting pressure equipment, reduces the connection cost, achieves high bending strength and acid-base corrosion resistance of ceramic connectors, and is universally applicable to a variety of ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430981A_ABST
    Figure CN119430981A_ABST
Patent Text Reader

Abstract

The invention relates to a ceramic material universal connection method based on passive pressure, and belongs to the technical field of ceramic part connection methods. The invention discloses a ceramic material universal connection method based on passive pressure, which comprises the following steps: coating the surface of a first ceramic piece with connection slurry, placing a second ceramic piece, and stacking according to a sandwich structure of the first ceramic piece, the connection slurry and the second ceramic piece, the two sides of the sandwich structure are clamped through a low-thermal-expansion-coefficient C / C flat plate and a differential-thermal-expansion-coefficient flat plate respectively and fixed through low-thermal-expansion-coefficient C / C bolts; and sintering to realize connection. According to the universal ceramic material connecting method based on the passive pressure, flat plates with different thermal expansion coefficients are adopted for clamping and fixed through C / C bolts, thermal stress is generated through limited thermal expansion of ceramics and flat plate clamps with different thermal expansion coefficients at the high temperature, and traditional high-pressure equipment is replaced for providing pressure; the connection pressure equipment dependence is greatly reduced, and the connection cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic component connection methods and relates to a universal ceramic material connection method based on passive pressure. Background Art

[0002] Ceramic materials have good high temperature strength, low thermal expansion coefficient, excellent thermal shock resistance, corrosion resistance, and wear resistance. They are widely used in aerospace, petroleum, chemical industry, machinery and other fields, and are currently receiving more and more attention. With the rapid development of aerospace, national defense, military, automobile and other fields, there is an urgent need for large-scale and complex advanced ceramic material structural parts. However, the high brittleness, low ductility and high hardness of ceramic materials make their processing performance poor. Under the current level of industrial development, the preparation of large and complex silicon carbide parts is difficult and the production cost is high. Connecting simple ceramic parts through connection technology is an effective method. Advanced connection technology makes it possible to manufacture large and complex ceramic material parts, which is of great significance to industrial development.

[0003] A good connection interface should maximize its continuity in basic physical and chemical properties (lattice, thermal conductivity, electrical conductivity, thermal expansion coefficient), mechanical behavior (no significant change in elastic modulus), thermodynamic stability (no reaction at the interface during application), etc. Therefore, the development direction of ceramic connection will focus on the connection material system in which the connection layer product is homogeneous with the base material. At present, the diffusion welding method is widely used. After the ceramic parts to be connected are stacked, homogeneous connection is achieved at 2000-2400℃ and 20-25Mpa high pressure. In order to reduce the connection temperature, relevant scholars have developed a nano-impregnation transient liquid phase (NITE) connection method, which uses nano-powders homogeneous with the base as raw materials and combines sintering aids to achieve high-density ceramic connection under a certain pressure. Then Northwestern Polytechnical University proposed a new field-induced flash joining (Flash joining, FJ) technology, which can connect ceramic materials in a very short time (seconds) by applying a DC electric field exceeding the threshold to ion-conducting ceramic materials. Related scholars have used the liquid phase formed at the interface between Dy3Si2C2 and SiC and squeezed it out under pressure to achieve seamless connection of SiC ceramics. However, diffusion welding, NITE connection, electric field assistance, flash burning and other connection methods are very demanding and usually need to be carried out under high temperature (≥1800℃) and high pressure (≥10MPa). They all rely on pressure equipment to provide active pressure, which greatly increases the connection cost and makes it difficult to achieve industrial production. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned problems existing in the prior art and to propose a universal connection method for ceramic materials based on passive pressure, which clamps the ceramic parts to be connected after stacking by C / C plates and low thermal expansion coefficient plates, and fixes them with C / C bolts, so that the prepared ceramic connecting parts have better bending strength and acid and alkali corrosion resistance.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A universal ceramic material connection method based on passive pressure, the connection method comprising:

[0007] After the connection slurry is coated on the surface of the first ceramic part, the second ceramic part is placed, and the first ceramic part-connection slurry-second ceramic part are stacked in a sandwich structure, and a low thermal expansion coefficient C / C plate and a differential thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with low thermal expansion coefficient C / C bolts; and then sintering is performed to achieve connection;

[0008] The thermal expansion coefficient of the differential thermal expansion coefficient plate is 0.1×10 -6 ~30×10 -6 / ℃, the thermal expansion coefficient of low thermal expansion coefficient C / C bolts is 0~2×10 -6 / ℃.

[0009] Preferably, the thermal expansion coefficient of the C / C bolt is 0 to 1×10 -6 / ℃.

[0010] Preferably, a low thermal expansion coefficient C / C plate and a differential thermal expansion coefficient plate are clamped on both sides of the sandwich structure and fixed with low thermal expansion coefficient C / C bolts, and the pre-tightening force of the bolts and the two plates is 20 to 30 N·m.

[0011] Preferably, during the sintering process, the thermal stress of the sandwich structure of the first ceramic member-connecting slurry-second ceramic member is 0.5-5 GPa.

[0012] Preferably, the differential thermal expansion coefficient plate includes one or more of a graphite plate, an alumina ceramic plate, a silicon carbide ceramic plate, and a titanium boride ceramic plate.

[0013] More preferably, the thermal expansion coefficient of the graphite plate is 5×10 -6 ~25×10 -6 / ℃;

[0014] The thermal expansion coefficient of the alumina ceramic plate is 5.5×10 -6 ~8.9×10 -6 / ℃; the thermal expansion coefficient of silicon carbide ceramic plate is 4.4×10-6 ~6.5×10 -6 / ℃;

[0015] The thermal expansion coefficient of the titanium boride ceramic plate is 6.1×10 -6 ~8.2×10 -6 / ℃.

[0016] Preferably, the thermal expansion coefficient of the C / C plate is 0 to 5×10 -6 / ℃.

[0017] Preferably, the plate with differential thermal expansion coefficient has a thickness of 1 to 130 mm, and its length and width are greater than those of the first ceramic piece and the second ceramic piece.

[0018] More preferably, the thickness of the differential thermal expansion coefficient plate is 10 to 50 mm.

[0019] Preferably, the thickness of the C / C flat plate is 1 to 130 mm, and the length and width are larger than the first ceramic piece and the second ceramic piece.

[0020] More preferably, the thickness of the C / C flat plate is 10 to 50 mm.

[0021] Preferably, the first ceramic component and the second ceramic component are independently selected from one or more of oxide ceramics, carbide ceramics and boride ceramics.

[0022] Preferably, the connection slurry includes ceramic powder, sintering aid, dispersant, binder and solvent.

[0023] More preferably, the connection slurry includes ceramic powder, sintering aid, dispersant, binder and solvent in a mass ratio of (40-70):(1-12):(0.8-6):(0.1-1.4):(45-80).

[0024] More preferably, the solid content of the connection slurry is 30 to 70 wt %.

[0025] More preferably, the solid content of the connecting slurry is 45 to 60 wt %.

[0026] More preferably, the average particle size of the ceramic powder is 1 to 200 nm.

[0027] Further preferably, the dispersant includes one or more of polyvinyl pyrrolidone, polyacrylamide, and phosphate; the binder includes one or more of polyvinyl alcohol, polyvinyl butyral, and phenolic resin; and the solvent includes one or more of distilled water, anhydrous ethanol, ethylene glycol, and acetone.

[0028] More preferably, the sintering aid includes one or more of B4C, carbon black, Al2O3, MgO, Y2O3, Al2O3-Y2O3, AlN, Al4C3-B4C, Al4SiC4, and borax. More preferably, when the ceramic part is silicon carbide ceramic, the ceramic powder is silicon carbide powder; when the ceramic part is boron carbide ceramic, the ceramic powder is boron carbide powder; when the ceramic part is alumina ceramic, the ceramic powder is alumina powder; when the ceramic part is titanium diboride ceramic, the ceramic powder is titanium diboride powder.

[0029] Preferably, the sintering temperature is 1000-2200° C., and the sintering time is 0.1-10 h.

[0030] More preferably, the sintering temperature is 1400-2100° C., and the sintering time is 0.5-5 h.

[0031] Preferably, the universal ceramic material connection method based on passive pressure comprises:

[0032] (1) mixing silicon carbide powder, a sintering aid, a dispersant, a binder, and a solvent, and ball-milling the mixture to obtain a connecting slurry having a solid content of 45 to 60 wt %;

[0033] (2) Two silicon carbide ceramics are ultrasonically cleaned and dried to serve as the first ceramic member and the second ceramic member; after the connection slurry is coated on the surface of the first ceramic member, the second ceramic member is placed thereon, and the two ceramic members are stacked in a sandwich structure of the first ceramic member-connection slurry-second ceramic member; a C / C plate and a low thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with C / C bolts; the thermal expansion coefficient of the differential thermal expansion coefficient plate is 0.1×10 -6 ~30×10 -6 / ℃, the thermal expansion coefficient of low thermal expansion coefficient C / C bolts is 0~2×10 -6 / ℃; then sinter at 1700-1900℃ in an inert gas for 0.5-2h to achieve connection.

[0034] Preferably, the universal ceramic material connection method based on passive pressure comprises:

[0035] (1) mixing alumina powder, a sintering aid, a dispersant, a binder, and a solvent and grinding them into a slurry to obtain a connecting slurry with a solid content of 45 to 60 wt %;

[0036] (2) Two alumina ceramics are ultrasonically cleaned and dried to serve as the first ceramic member and the second ceramic member; after the connection slurry is coated on the surface of the first ceramic member, the second ceramic member is placed thereon, and the two ceramic members are stacked in a sandwich structure of the first ceramic member-connection slurry-second ceramic member; a C / C plate and a low thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with C / C bolts; the thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10 -6 ~10×10 -6 / ℃, the thermal expansion coefficient of C / C bolts is 0~2×10 -6 / ℃; then sinter at 1400-1700℃ in an inert gas for 0.5-2h to achieve connection.

[0037] Preferably, the universal ceramic material connection method based on passive pressure comprises:

[0038] (1) mixing boron carbide powder, a sintering aid, a dispersant, a binder, and a solvent and ball-milling the mixture to obtain a connecting slurry having a solid content of 45 to 60 wt %;

[0039] (2) Two boron carbide ceramics are ultrasonically cleaned and dried to serve as a first ceramic member and a second ceramic member; after a connection slurry is coated on the surface of the first ceramic member, the second ceramic member is placed thereon, and the first ceramic member-connection slurry-second ceramic member are stacked in a sandwich structure; a C / C plate and a low thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with C / C bolts; the thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10 -6 ~10×10 -6 / ℃, the thermal expansion coefficient of C / C bolts is 0~2×10 -6 / ℃; then sinter at 1950-2100℃ in an inert gas for 0.5-2h to achieve connection.

[0040] Preferably, the universal ceramic material connection method based on passive pressure comprises:

[0041] (1) mixing titanium diboride powder, a sintering aid, a dispersant, a binder, and a solvent and grinding them into a slurry to obtain a connecting slurry with a solid content of 45 to 60 wt %;

[0042] (2) Two titanium diboride ceramics are ultrasonically cleaned and dried to serve as the first ceramic member and the second ceramic member; after the connection slurry is coated on the surface of the first ceramic member, the second ceramic member is placed thereon, and the two ceramic members are stacked in a sandwich structure of the first ceramic member-connection slurry-second ceramic member; a C / C plate and a low thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with C / C bolts; the thermal expansion coefficient of the low thermal expansion coefficient plate is 0.1×10 -6 ~10×10 -6 / ℃, the thermal expansion coefficient of C / C bolts is 0~2×10 -6 / ℃; then sinter at 1750-2000℃ in an inert gas for 0.5-2h to achieve connection.

[0043] A ceramic connecting piece comprises a first ceramic piece, an intermediate connecting layer and a second ceramic piece, wherein the thickness of the intermediate connecting layer is 0.1-80 μm.

[0044] Preferably, the thickness of the intermediate connection layer is 1 to 45 μm.

[0045] More preferably, the thickness of the intermediate connection layer is 4 to 30 μm.

[0046] Preferably, the weight loss rate of the intermediate connecting layer after being corroded by 6 mol / L NaOH solution at 100°C / 24h is less than 30 mg / dm 2 The weight loss rate of the intermediate connection layer after being corroded by 3mol / L sulfuric acid solution at 100℃ / 24h is less than 7mg / dm 2 .

[0047] Preferably, the intermediate connection layer of the ceramic connection piece has a bending strength of 120 to 550 MPa at room temperature and a bending strength of 80 to 520 MPa at 1400°C.

[0048] Preferably, the intermediate connection layer of the silicon carbide ceramic connection piece has a bending strength of 280 to 550 MPa at room temperature and a bending strength of 240 to 520 MPa at 1400°C.

[0049] Preferably, the intermediate connection layer of the alumina ceramic connection piece has a bending strength of 330-450 MPa at room temperature and a bending strength of 240-370 MPa at 1400°C.

[0050] Preferably, the intermediate connection layer of the boron carbide ceramic connection piece has a bending strength of 400-470 MPa at room temperature and a bending strength of 370-420 MPa at 1400°C.

[0051] Preferably, the bending strength of the intermediate connection layer of the titanium diboride ceramic connection piece at room temperature is 120-220 MPa, and the bending strength at 1400° C. is 80-180 MPa.

[0052] A ceramic connector is used in the fields of aerospace, chemical industry, heat exchange device packaging, semiconductors, chemical industry, coatings, refractory materials, cutting tools, and electronic devices.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] 1. The present invention uses flat plates with different thermal expansion coefficients to clamp on both sides of the sandwich structure of the first ceramic part-connecting slurry-second ceramic part and uses C / C bolts to fix them. Thermal stress is generated by the restricted thermal expansion of the ceramic itself and the flat plate clamps with different thermal expansion coefficients at high temperatures, replacing traditional high-pressure equipment to provide pressure, greatly reducing the dependence on connection pressure equipment and reducing connection costs.

[0055] 2. Compared with traditional graphite clamping, the clamping device combination of the present invention generates GPa-level thermal stress at high temperature, and can effectively reduce the sintering temperature of the ceramic connector connection process without external pressure.

[0056] 3. The particle size of the ceramic powder in the connection slurry of the present invention is relatively small, which further reduces the sintering temperature of the ceramic connection parts during the connection process.

[0057] 4. The present invention can meet the connection requirements of various ceramic materials such as oxides, carbides, borides, etc. by regulating the clamping plate material, connection slurry and connection temperature, and has universal applicability.

[0058] 5. The intermediate connection layer of the ceramic connector of the present invention is thin, has excellent connection performance, and has good acid and alkali corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 Schematic diagram of the universal connection method of ceramic materials based on passive pressure of the present invention (a) and thermal stress distribution diagram of Example 1 based on COMSOL simulation (b).

[0060] Figure 2 This is a microstructure diagram of the silicon carbide ceramic connector in Example 2 of the present invention.

[0061] Figure 3 It is the traditional graphite fixture used in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The following are specific embodiments of the present invention, which further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0063] Unless otherwise specified, the materials used in the present invention are conventional commercial products, and the methods used are conventional technical means.

[0064] The plate with differential thermal expansion coefficient used in the present invention includes one or more of a graphite plate, an alumina ceramic plate, a silicon carbide ceramic plate, and a titanium boride ceramic plate; wherein the thermal expansion coefficient of the graphite plate is 5×10 -6 ~25×10 -6 / ℃; the thermal expansion coefficient of the alumina ceramic plate is 5.5×10 -6 ~8.9×10-6 / ℃; the thermal expansion coefficient of silicon carbide ceramic plate is 4.4×10 -6 ~6.5×10 -6 / ℃; the thermal expansion coefficient of the titanium boride ceramic plate is 6.1×10 -6 ~8.2×10 -6 / ℃.

[0065] The thermal expansion coefficient of the C / C plate is 0 to 5×10 -6 / ℃;

[0066] The length and width of the differential thermal expansion coefficient plate and the C / C plate are both greater than those of the first ceramic piece and the second ceramic piece.

[0067] The thickness of the first ceramic piece and the second ceramic piece used in the present invention is 10-30 mm.

[0068] The testing standard of the bending strength of the present invention is GB / T6569-2006 / ISO14704:2000.

[0069] Example 1

[0070] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0071] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 45 g of silicon carbide powder (average particle size 40 nm), 5 g of Al2O3-Y2O3 (YAG) sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece and the second ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25Nm, and then placed in a high-temperature sintering furnace and sintered at 1850℃ for 1h in an argon environment to achieve ceramic connection to obtain a ceramic connector.

[0072] Figure 1 Schematic diagram of the universal ceramic material connection method based on passive pressure in this embodiment (a) and the thermal stress distribution diagram of the connection process in this embodiment 1 based on COMSOL simulation. It can be seen that during the sintering process, the thermal stress range of the connection contact surface reaches 2.56~4.72GPa.

[0073] The thickness of the middle connection layer of the silicon carbide ceramic connector is 5 μm, the bending strength at room temperature is 281 MPa, and the bending strength at 1400°C is 240 MPa. The weight loss rate of the ceramic joint (middle connection layer) after being corroded by 6 mol / L NaOH solution at 100°C / 24h is 25 mg / dm 2 After being corroded by 3 mol / L sulfuric acid solution at 100℃ / 24h, the weight loss rate is 5 mg / dm 2 .

[0074] The silicon carbide ceramic connector in this embodiment can be widely used in the fields of aerospace, chemical industry and heat exchange device packaging.

[0075] Example 2

[0076] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0077] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 45 g of silicon carbide powder (average particle size 40 nm), 5 g of Al4SiC4 sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace. In an argon environment, it is sintered at 1950℃ for 1h to perform ceramic connection to obtain a ceramic connector.

[0078] The microstructure of the silicon carbide ceramic connector in this embodiment is shown in FIG. Figure 2 As shown, the thickness of the intermediate connection layer of the silicon carbide ceramic connector is 10.6μm, the bending strength at room temperature is 375MPa, the bending strength at 1400℃ is 310MPa, and the weight loss rate of the ceramic joint after being corroded by 6mol / L NaOH solution at 100℃ / 24h is 5mg / dm 2 After being corroded by 3 mol / L sulfuric acid solution at 100℃ / 24h, the weight loss rate is 2mg / dm 2 .

[0079] The silicon carbide ceramic connector in this embodiment can be widely used in the fields of aerospace, chemical industry and heat exchange device packaging.

[0080] Example 3

[0081] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0082] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 45 g of silicon carbide powder (average particle size 40 nm), 5 g of Al4SiC4 sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 30 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace. In an argon environment, it is sintered at 1950℃ for 1h to perform ceramic connection to obtain a ceramic connector.

[0083] The thickness of the middle connection layer of the silicon carbide ceramic connector is 9 μm, the bending strength at room temperature is 416 MPa, the bending strength at 1400°C is 362 MPa, and the weight loss rate of the ceramic joint after being corroded by 6 mol / L NaOH solution at 100°C / 24h is 3 mg / dm 2 After being corroded by 3 mol / L sulfuric acid solution at 100℃ / 24h, the weight loss rate is 1mg / dm 2 .

[0084] The silicon carbide ceramic connector in this embodiment can be widely used in the fields of aerospace, chemical industry and heat exchange device packaging.

[0085] Compared with Example 2, the difference is that the thickness of the graphite plate in this embodiment is increased, and the bending strength and corrosion resistance of the ceramic connector are improved. If the thickness of the graphite plate continues to increase, the bending strength and corrosion resistance continue to improve, and the improvement rate slows down until it stabilizes.

[0086] Example 4

[0087] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0088] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 45 g of silicon carbide powder (average particle size 40 nm), 5 g of Al4SiC4 sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick titanium boride ceramic plate were used to clamp the two sides of the sandwich structure, and then a 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace. In an argon environment, it is sintered at 1950℃ for 1h to perform ceramic connection to obtain a ceramic connector.

[0089] The thickness of the middle connection layer of the silicon carbide ceramic connector is 12μm, the bending strength at room temperature is 332MPa, the bending strength at 1400℃ is 278MPa, and the weight loss rate of the ceramic joint after being corroded by 6mol / L NaOH solution at 100℃ / 24h is 12mg / dm 2 After being corroded by 3 mol / L sulfuric acid solution at 100℃ / 24h, the weight loss rate is 2.5 mg / dm 2 .

[0090] The silicon carbide ceramic connector in this embodiment can be widely used in the fields of aerospace, chemical industry and heat exchange device packaging.

[0091] Compared with Example 2, the difference is that this embodiment uses a C / C plate and a titanium boride ceramic plate for clamping. The thermal expansion coefficient of the titanium boride ceramic plate is smaller than that of the graphite plate, resulting in a decrease in the thermal stress of the connection surface, resulting in poor bending strength and corrosion resistance.

[0092] Example 5

[0093] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0094] Two alumina ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 49 g alumina powder (average particle size 40 nm), 1 g MgO sintering aid, 2 g polyvinyl pyrrolidone, 0.5 g polyvinyl butyral and 50 g ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace. In an argon environment, it is sintered at 1450℃ for 1h to perform ceramic connection to obtain a ceramic connector.

[0095] The thickness of the middle connection layer of the alumina ceramic connection piece is 30 μm, the bending strength at room temperature is 340 MPa, and the bending strength at 1400° C. is 260 MPa.

[0096] The alumina ceramic connector in this embodiment can be widely used in the fields of semiconductors, chemical industry, etc.

[0097] Example 6

[0098] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0099] Two alumina ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 49 g alumina powder (average particle size 40 nm), 1 g MgO sintering aid, 2 g polyvinyl pyrrolidone, 0.5 g polyvinyl butyral and 50 g ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.005×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace. In an argon environment, it is sintered at 1450℃ for 1h to perform ceramic connection to obtain a ceramic connector.

[0100] The thickness of the middle connection layer of the alumina ceramic connection piece is 21 μm, the bending strength at room temperature is 383 MPa, and the bending strength at 1400° C. is 303 MPa.

[0101] The alumina ceramic connector in this embodiment can be widely used in the fields of semiconductors, chemical industry, etc.

[0102] Compared with Example 5, the difference is that in this embodiment, C / C bolts with a thermal expansion coefficient infinitely close to zero are used for clamping and fixing, so that the bending strength of the ceramic connector is further improved.

[0103] Example 7

[0104] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0105] Two boron carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 45 g of boron carbide powder (average particle size 40 nm), 5 g of Y2O3 sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace and sintered at 2000℃ for 1h in an argon environment to achieve ceramic connection to obtain a ceramic connector.

[0106] The thickness of the middle connection layer of the boron carbide ceramic connection piece is 11 μm, the bending strength at room temperature is 424 MPa, and the bending strength at 1400° C. is 383 MPa.

[0107] The boron carbide ceramic connecting piece in this embodiment can be widely used in the fields of superhard materials, aerospace, refractory materials, nuclear industry, etc.

[0108] Example 8

[0109] The universal ceramic material connection method based on passive pressure in this embodiment includes the following steps:

[0110] Two titanium diboride ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece. 55 g of titanium diboride powder (average particle size 40 nm), 5 g of borax sintering aid, 1 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 40 g of ethanol were stirred and mixed and ball-milled for 8 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic piece by screen printing. The first ceramic piece-connecting slurry-second ceramic piece was stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace and sintered at 1900℃ for 1h in an argon environment to achieve ceramic connection to obtain a ceramic connector.

[0111] The thickness of the intermediate connection layer of the titanium diboride ceramic connection piece is 22 μm, the bending strength at room temperature is 146 MPa, and the bending strength at 1400° C. is 112 MPa.

[0112] The titanium diboride ceramic connector in this embodiment can be widely used in the fields of coatings, refractory materials, cutting tools, electronic devices, etc.

[0113] Comparative Example 1

[0114] The ceramic material connection method based on passive pressure in this comparative example comprises the following steps:

[0115] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic piece and the second ceramic piece; 45 g of silicon carbide powder (average particle size 40 nm), 5 g of Al2O3-Y2O3 (YAG) sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 hours to obtain a connecting slurry; the connecting slurry was applied to the surface of the first ceramic piece by screen printing; the first ceramic piece-connecting slurry-second ceramic piece were stacked in a sandwich structure, and the connecting slurry was used as follows: Figure 3 The conventional one-piece graphite fixture shown is clamped with a preload of 25 N·m, and then placed in a high-temperature sintering furnace, sintered at 1850°C for 1 hour in an argon environment to perform ceramic connection to obtain a ceramic connector.

[0116] The thickness of the middle connection layer of the silicon carbide ceramic connection piece is 86 μm, the bending strength at room temperature is 105 MPa, and the bending strength at 1400° C. is 56 MPa.

[0117] Comparative Example 2

[0118] The universal ceramic material connection method based on passive pressure in this comparative example comprises the following steps:

[0119] Two silicon carbide ceramics were ultrasonically cleaned and dried to serve as the first ceramic member and the second ceramic member. 45 g of silicon carbide powder (average particle size 500 nm), 5 g of Al2O3-Y2O3 (YAG) sintering aid, 2 g of polyvinyl pyrrolidone, 0.5 g of polyvinyl butyral and 50 g of ethanol were stirred and mixed and ball-milled for 6 h to obtain a connecting slurry. The connecting slurry was applied to the surface of the first ceramic member by screen printing. The first ceramic member-connecting slurry-second ceramic member were stacked in a sandwich structure, and a 10 mm thick C / C plate and a 10 mm thick graphite plate were used to clamp the two sides of the sandwich structure, and then a thermal expansion coefficient of 0.5×10 -6 / ℃ C / C bolts are clamped and fixed with a pre-tightening force of 25N·m, and then placed in a high-temperature sintering furnace and sintered at 1850℃ for 1h in an argon environment to perform ceramic connection to obtain a ceramic connector.

[0120] The thickness of the middle connection layer of the silicon carbide ceramic connection piece is 35 μm, the bending strength at room temperature is 175 MPa, and the bending strength at 1400° C. is 156 MPa.

[0121] Compared with Example 1, the difference is that the average particle size of the silicon carbide powder in this comparative example increases, resulting in reduced bending strength and corrosion resistance.

[0122] In summary, the present invention satisfies the connection of various ceramic materials such as oxides, carbides, borides, etc. by regulating the clamping plate material, connecting slurry and connecting temperature, and has universal applicability; and the ceramic connectors prepared by the universal connection method of ceramic materials based on passive pressure of the present invention have good bending strength and acid and alkali corrosion resistance.

[0123] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A universal ceramic material connection method based on passive pressure, characterized in that: The connection method includes: After the connection slurry is coated on the surface of the first ceramic part, the second ceramic part is placed, and the first ceramic part-connection slurry-second ceramic part are stacked in a sandwich structure, and a low thermal expansion coefficient C / C plate and a differential thermal expansion coefficient plate are clamped on both sides of the sandwich structure, and fixed with low thermal expansion coefficient C / C bolts; and then sintering is performed to achieve connection; The thermal expansion coefficient of the differential thermal expansion coefficient plate is 0.1×10 -6 ~30×10 -6 / ℃, the thermal expansion coefficient of low thermal expansion coefficient C / C bolts is 0~2×10 -6 / ℃.

2. The universal ceramic material connection method based on passive pressure according to claim 1 is characterized in that: The differential thermal expansion coefficient plate includes one or more of a graphite plate, an alumina ceramic plate, a silicon carbide ceramic plate, and a titanium boride ceramic plate.

3. The universal ceramic material connection method based on passive pressure according to claim 1 is characterized in that: The thermal expansion coefficient of the C / C plate is 0 to 5×10 -6 / ℃.

4. The universal ceramic material connection method based on passive pressure according to claim 1, characterized in that: The thickness of the differential thermal expansion coefficient plate is 1-130 mm, and its length and width are larger than the first ceramic piece and the second ceramic piece; the thickness of the C / C plate is 1-130 mm, and its length and width are larger than the first ceramic piece and the second ceramic piece.

5. The universal ceramic material connection method based on passive pressure according to claim 1, characterized in that: The first ceramic component and the second ceramic component are independently selected from one or more of oxide ceramics, carbide ceramics, and boride ceramics.

6. The universal ceramic material connection method based on passive pressure according to claim 1, characterized in that: The connection slurry comprises ceramic powder, sintering aid, dispersant, binder and solvent; the solid content of the connection slurry is 30-70wt%.

7. The passive pressure-based universal ceramic material connection method according to claim 6, characterized in that: The average particle size of the ceramic powder is 1 to 200 nm; the sintering aid includes one or more of B4C, carbon black, Al2O3, MgO, Y2O3, Al2O3-Y2O3, AlN, Al4C3-B4C, Al4SiC4, and borax.

8. A ceramic connector, characterized in that: It is manufactured by the universal ceramic material connection method based on passive pressure according to any one of claims 1 to 7, and comprises a first ceramic part, an intermediate connection layer, and a second ceramic part, wherein the thickness of the intermediate connection layer is 0.1 to 80 μm.

9. The ceramic connector according to claim 8, characterized in that: The weight loss rate of the intermediate connection layer after being corroded by 6 mol / L NaOH solution at 100°C / 24h is less than 30 mg / dm 2 The weight loss rate of the intermediate connection layer after being corroded by 3mol / L sulfuric acid solution at 100℃ / 24h is <7mg / dm 2 The bending strength of the intermediate connecting layer at room temperature is 120-550 MPa, and the bending strength at 1400°C is 80-520 MPa.

10. Application of the ceramic connector according to claim 8 in the fields of aerospace, chemical industry, heat exchange device packaging, semiconductor, chemical industry, coating, refractory material, cutting tool, and electronic device.

Citation Information

Patent Citations

  • Method of connecting sheets by thermal self-pressing

    CN103464907A

  • Method for producing connecting element and connecting element

    CN112049843A

  • Connection method of silicon carbide ceramics based on liquid phase sintering

    CN114478043A

  • Method for bonding inorganic fiber to ceramic body with high heat resistance

    JP2003128472A

  • Silicon carbide ceramic joined body, and manufacturing method for the same

    JP2014094855A